Efavirenz Intoxication Due to a New Cyp2B6 Constellation. Issue 5 (July 2013) - Anagnostopoulos, Alexia; Rotger, Margalida; Aouri, Manel; Kuster, Stefan P; Telenti, Amalio; Décosterd, Laurent A; Günthard, Huldrych F
Here, we describe severe neuropsychiatric symptoms in an HIV-positive Asian man with extremely high efavirenz plasma levels while receiving standard treatment with efavirenz/tenofovir/emtricitabine fixed-dose regimen. Genetic examination revealed compound homozygosity for loss-of-function alleles of CYP2B6, including coding for a rare truncated protein. Neuropsychiatric symptoms resolved completely after efavirenz discontinuation.